Form and Function of the Nasal Tip: Reorienting and Reshaping the Lateral Crus - Hamilton, Grant S., III (Facial Plastic Surgery, 2016)
Dysfunction of the external nasal valve affects both the form and function of the nose. Successful treatment of these problems is dependent on proper analysis and diagnosis of the aberrant anatomy. Cephalic malpositioning of the lateral crura has been described for nearly 30 years. Repositioning of the lateral crura in a more caudal orientation with lateral crural strut grafts will correct aesthetic abnormalities and reinforce the external nasal valve. Sagittal malpositioning has been more recently described and also has deleterious effects on both the shape of the nasal tip and breathing. Reorienting the short axis of the lateral crus is another powerful tool for the rhinoplasty surgeon to correct the weak and narrow external nasal valve.
Keywords: rhinoplasty; external nasal valve; cephalically malpositioned lateral crura; sagittally malpositioned lateral crura; nasal obstruction